Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijms222011226
|View full text |Cite
|
Sign up to set email alerts
|

In Silico and In Vivo Analysis of Amino Acid Substitutions That Cause Laminopathies

Abstract: Mutations in the LMNA gene cause diseases called laminopathies. LMNA encodes lamins A and C, intermediate filaments with multiple roles at the nuclear envelope. LMNA mutations are frequently single base changes that cause diverse disease phenotypes affecting muscles, nerves, and fat. Disease-associated amino acid substitutions were mapped in silico onto three-dimensional structures of lamin A/C, revealing no apparent genotype–phenotype connections. In silico analyses revealed that seven of nine predicted partn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 83 publications
(152 reference statements)
0
18
0
Order By: Relevance
“…The positions of the amino acid changes examined in this study are shown with the corresponding human amino acid changes in parentheses. (B) Three-dimensional model of full-length human lamin A ( Hinz et al, 2021 ) with the position of the amino acid changes in the head and rod domain indicated by arrows. The positions of amino acid changes in the Ig fold are indicated in the magnified view (panel C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The positions of the amino acid changes examined in this study are shown with the corresponding human amino acid changes in parentheses. (B) Three-dimensional model of full-length human lamin A ( Hinz et al, 2021 ) with the position of the amino acid changes in the head and rod domain indicated by arrows. The positions of amino acid changes in the Ig fold are indicated in the magnified view (panel C).…”
Section: Resultsmentioning
confidence: 99%
“…The amino acid changes under investigation were mapped onto the three-dimensional structure of lamin A/C that is based on a combination of experimental data and in silico predictions ( Figure 1B ) ( Krimm et al, 2002 ; Strelkov et al, 2004 ; Lilina et al, 2020 ; Hinz et al, 2021 ). The amino acid residues S22 and K32 map within a short-predicted alpha-helical region of the head domain ( Figure 1B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 400 mutations in LMNA have been linked to diseases collectively called laminopathies, the majority affecting muscle [ 28 , 29 , 30 ]. Most LMNA DNA lesions are point mutations that give rise to single amino acid substitutions throughout the head, rod, and tail domain, which possess an Ig-like fold [ 31 , 32 ]. Several studies have attempted to establish a correlation between the genotype and disease phenotype; however, such correlations are limited [ 6 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lamin A consists of a 42‐residue lamin‐specific 1B insert and constitutes almost half of the super‐helix turn in the middle of the 1B domain, with which it preserves heptad periodicity for dimer formation, conserves the positions of the distal coiled‐coil regions for tetramer formation, and provides additional interdimer molecular contacts 6–9 . Thus, mutations in the rod domain of lamin A could directly affect intermolecular interactions and/or protein stability, and may lead to progeroid laminopathies such as APS and A‐WS 9,10 …”
Section: Introductionmentioning
confidence: 99%